2020
DOI: 10.3390/antibiotics9030110
|View full text |Cite
|
Sign up to set email alerts
|

The Use of a Non-Absorbable Membrane as an Occlusive Barrier for Alveolar Ridge Preservation: A One Year Follow-Up Prospective Cohort Study

Abstract: The aims of this study were to obtain preliminary data and test the clinical efficacy of a novel nonporous dense-polytetrafluoroethylene (d-PTFE) membrane (permamem®, botiss) in alveolar ridge preservation (ARP) procedures with a flapless approach. A traumatic extraction was performed in the premolar maxillary area, and a d-PTFE membrane was used to seal the alveolar cavity: no biomaterial was used to graft the socket and the membrane was left intentionally exposed and stabilized with sutures. The membrane was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Both kinds are pure dense PTFE, without reinforcements, containing surface macro-roughness features (ridges vs. dents), thus differing only in physical features and polymer microstructure. One of them (designated PTFE-W) is well-established in clinical use [ 15 , 19 ], while the other one (PTFE-B) is new but proved to be effective in alveolar ridge preservation [ 31 ]. The effect of diverse microstructural features of chemically identical materials on bacterial adhesion has been observed for other materials; for example, bacterial adhesion was affected by crystalline vs. amorphous phase on Ti-based material for orthopaedic implants [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both kinds are pure dense PTFE, without reinforcements, containing surface macro-roughness features (ridges vs. dents), thus differing only in physical features and polymer microstructure. One of them (designated PTFE-W) is well-established in clinical use [ 15 , 19 ], while the other one (PTFE-B) is new but proved to be effective in alveolar ridge preservation [ 31 ]. The effect of diverse microstructural features of chemically identical materials on bacterial adhesion has been observed for other materials; for example, bacterial adhesion was affected by crystalline vs. amorphous phase on Ti-based material for orthopaedic implants [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…A commonly applied socket preservation technique involves a flapless approach and bone grafting of the residual socket to prevent bone loss immediately after extraction [ 7 , 8 ]. However, it was demonstrated that a lack of socket sealing could lead to clinical failures [ 26 , 27 ]. To overcome these limitations, various soft tissue management techniques have been proposed, including advanced coronal flap [ 28 ], epithelial-connective soft tissue graft [ 29 ], resorbable porcine collagen matrix [ 11 ], or intentionally exposed, not resorbable membranes [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…A few types of coronal seal materials have been used to block infiltration of soft tissue into the lower bone graft area in flapless ridge preservation; these include membranes and collagen plugs [16,20,31,41]. Sockets have previously been sealed with a porcine collagen matrix, epithelial connective tissue grafts or membranes, and these approaches all yielded the desired outcomes [16,20,[41][42][43]. Currently, leukocyte-and platelet-rich fibrin membrane is also used to seal post-extraction sockets [44].…”
Section: Methodsmentioning
confidence: 99%